KEBIJAKAN UMAR BIN KHATTAB DALAM MENGHADAPI PANDEMI AMWAS - Syafri Gunawan (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2021)
This paper traces the occurrence of the 'Amwas outbreak by involving the social conditions of the community through the records of historians as well as an analysis of the policies of successful leaders in the past in tackling disease outbreaks, including the caliph Umar bin Khattab. So the problem that will be answered in this paper is how the policies of the caliph Umar bin Khattab in dealing with disease outbreaks in his time. So the method used to answer this problem, the authors use descriptive qualitative methods, namely looking for answers from various literatures that explain the summary of the policies of the caliph Umar bin Khattab in tackling disease outbreaks. The finding that in policies during the reign of the caliph Umar bin Khattab there were also restrictions on community activities to prevent the circulation of the 'Amwas virus, the same as what was done in preventing the circulation of the Covid 19 virus that hit the world today.